Art Therapy, Community Building, Activism, and Outcomes - Feen-Calligan, Holly; Moreno, Julie; Buzzard, Emma (Frontiers in Psychology, 2018)
This article is a descriptive study of two groups who came together through service-learning: The first group is graduate art therapy students enrolled in a research class, who partnered with six community agencies to help them prepare assignments for undergraduate service-learning students in a subsequent semester. The art therapy research students also assisted the agencies with program evaluation. The second group is the six directors of the community agencies who were preparing for service-learning students enrolled in an art history class titled Art as A Social Practice. Service-learning is an experiential pedagogy where community service is integrated into an academic course, and where the services performed meet genuine community needs. The hyphen in service-learning represents the ideal that both the students and community agencies experience benefits from the relationship, although in reality, it is often the experiences of the students rather than the agencies that receive greater attention in the scholarly research literature. The present article places focus on the community agencies that, in the process of planning for service-learners, made two unexpected requests: First they requested that the service-learners stay longer than one semester, and secondly, they requested assistance with evaluating the effectiveness of their programs. This article is about the efforts to respond to these requests through the assistance of art therapy research students. With growing trends in community-based art therapy practice, greater attention to the community agencies where art therapists work is necessary and valuable to art therapy preparation. The present article describes six distinctive communities, illustrating new frontiers of practice. The research students’ experiences and the experiences of the community partners were assessed using qualitative methods that included pre and post-questionnaires, written reflections of students, interviews of agency directors and agency, student, and researcher focus group transcripts. This study will inform other art therapy programs who may want to use a service-learning approach to teaching research. A discussion of the promising practices of service-learning and research, as well as the challenges leads to recommendations for art therapy education.